SOME TENSILE PROPERTIES OF UNSATURATED POLYESTER RESIN REINFORCED WITH VARYING VOLUME FRACTIONS OF CARBON BLACK NANOPARTICLES (Nigerian Journal of Technology, 2008)
The recent emergence of nano science and nano technology has added another dimension to the staple of the modern composite technology. Instead of micron diameter fibres and particles, nano particles are being incorporated into polymer matrices to form a composite blend known as polymer nano composites (PNCs). This study investigated the tensile response of polyester composites reinforced with petroleum-based carbon black (CB) nano particles. The composites were prepared with 1 to 11% volume fractions of carbon black nanoparticles using manual and machine dispersion methods. Tensile samples of 165 ×19.5 × 3.2 mm3 prepared using ASTM D638 Standard were tested in a Hounsfield (Monsato) testing unit. Results showed that tensile strength, percentage elongation and tensile toughness at fracture increased as the volume fractions of carbon black nanoparticles increased from 1% to 5% in both manual and machine prepared composites. It is important to note that the maximum tensile strength and percentage elongation at fracture occurred at 5% carbon black and as the volume fraction increased above this, tensile strength and elongation at fracture decreased. The machine mixed composite showed the highest improvement in the above tensile properties at this low volume fraction. The tensile modulus of manual mixed composite decreased as CB volume fraction increased. In contrast, modulus of machine mixed composite was constant from 1% to 5% but increased as volume fractions increased from 7% to 11%. The above findings corroborated earlier findings in previous works which noted that nanocomposites have advantage over micro composites at low volume fractions especially with better dispersion of nanopariculates in polymer matrices.